Association between leukemia incidence and mortality and residential petrochemical exposure: A systematic review and meta-analysis. (December 2020) - Boonhat, Hathaichon; Lin, Ro-Ting
Highlights: We summarized the effects of petrochemical exposure on residents' leukemia. We included 13 observational studies, covering 9 countries and over 125, 000 people. Petrochemical exposure is associated with residents' leukemia incidence and mortality. The certainty of evidence was low for leukemia incidence and moderate for mortality. Abstract: Background: The global burden of leukemia, which grew by 19% from 2007 to 2017, poses a threat to human development and global cancer control. Factors contributing to this growth include massive industrial pollution, especially from large-scale petrochemical industry complexes (PICs). Globally, around 700 PICs are continuously operating. Data on the impact of PICs on leukemia incidence and mortality in residents are sparse and inconsistent. Objective: To determine the association between residential exposure to PICs and leukemia incidence and mortality using systematic review and meta-analysis. Methods: The studies were identified through seven databases (Clinical Key, Cochrane Library, EBSCOhost, Embase, PubMed, ScienceDirect, and Web of Science). We screened the eligibility of studies using following criteria: (1) observational studies that focused on residential exposure to PICs; (2) exposure group that was defined as residents living close to PICs; (3) outcome that was defined as all leukemia incidence and mortality; and (4) available population data. We applied the Grading of Recommendations Assessment, Development, and Evaluation to assess the certainty of evidence. The random-effects model used to estimate the pooled effects in the meta-analysis. Results: We identified thirteen epidemiologic studies (including eleven for leukemia incidence, one for leukemia mortality, and one for both), covering 125, 580 individuals from Croatia, Finland, Italy, Serbia, Spain, Sweden, Taiwan, the United Kingdom, and the United States. We found moderate certainty of evidence indicated the risk of leukemia incidence (relative risk [RR] = 1.18; 95% CI = 1.03–1.35) and mortality (RR = 1.26; 95% CI = 1.10–1.45) in residents living close to PICs. Our subgroup analysis found increased RRs for leukemia incidence in studies using distance-based exposure indicator (RR = 1.11; 95% CI = 1.00–1.23), and with longer follow-up periods (RR = 1.24; 95% CI = 1.06–1.45). Conclusion: Our analysis provides low-certainty evidence of increased leukemia incidence and moderate-certainty evidence of increased leukemia mortality among residents living close to PICs. While the global petrochemicals sector is growing, our findings suggest the need to consider disease prevention and pollution control measures during the development of PICs.